Abstract Book IV Congress of International Medical Ozone Federation (IMEOF) I Congress of the The Cuban Ozone Therapy Society (SCO), V Congress of Mexican Ozone Therapy Association (AMOZON) (Ozone Therapy Global Journal, 2015)
Libro de resúmenesIV Congress of International Medical Ozone Federation (IMEOF)I Congress of the The Cuban Ozone Therapy Society (SCO),V Congress of Mexican Ozone Therapy Association (AMOZON)Havana, Cuba,  Friday 27th – Sunday 29th November 2015.«Regularization, unity and science for worldwide ozone therapy”«Regularización, unidad y ciencia en pro de la ozono terapia mundial»